Social Studies Learning Media Integrated with Local Wisdom: A Perspective from Prospective Teachers - Agustina, Emilia (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to describe prospective teachers' views on the use of social studies learning media that integrate elements of local wisdom. The background of this study is based on the urgency of presenting contextual learning to better suit students' social and cultural realities. The research approach used is descriptive qualitative with data collection methods in the form of interviews, observations, and documentation studies. The subjects in this study were students of the social studies education study program who attended the instructional media course. The findings indicate that the majority of prospective teachers understand the importance of local wisdom as a meaningful learning resource and are able to explore the potential of local culture to be part of the social studies learning material. They also demonstrated innovation in creating learning media that highlight folklore, traditional games, and the surrounding environment. However, there are still obstacles, such as limited resources and access to relevant information. The conclusion of this study confirms that the integration of local wisdom into social studies learning media plays a strategic role in encouraging active student involvement and strengthening cultural identity. However, its implementation requires institutional support in the form of training and the provision of contextual learning resources.